Sweetpotato seed systems: A question of quantity and quality - International Potato Center (2011)
Techniques do exist to remove viruses, multiply plantlets in-vitro in tissue culture labs, and protect this disease-free foundation material in screen houses. This material is relatively expensive; hence the challenge remains to lower the cost of producing clean planting material, prevent its re-infection and demonstrate that farmers who utilize such materials reap worthwhile gains.